A mathematical model for sublimation of a thin film in trace explosive detection problem - Kudryashova, Olga B. (Molecules)
Here, we introduce an advanced mathematical model for the sublimation of thin films of explosives. The model relies on the Hertz–Knudsen–Langmuir (HKL) equation that describes the vaporization rate of an explosive and controls the mass exchange between the surface and the ambient air. The latest experimental data on sublimation and diffusion of 2,4,6-trinitrotoluene (TNT) monocrystals were factored in, as well as the data on the sublimation rate of hexogen (RDX), octogen (HMX), and picramide (TNA) traces. To advance the mathematical model we suggested previously, we took into account the structure of a substrate on which a thin explosive layer was deposited. The measurement problem of the sublimation rate and limits of an explosive arises from developing and advancing remote detection methods for explosives traces. Using mathematical modelling, we can identify a detectable quantity of a specific explosive under given conditions. We calculated the mass of the explosive in the air upon sublimation of thin explosive films from the surfaces over a wide range of the parameters in question and made conclusions regarding the application limits of the devised standoff trace explosive detection techniques.